Silicon carbide polishing composition and polishing method thereof

By using rutile titanium dioxide and calcium ion compositions, the problem of high polishing cost of silicon carbide is solved, and efficient polishing is achieved in the weak acid to alkaline range, reducing the risk of surface scratches.

CN119220183BActive Publication Date: 2025-04-18DONGGUAN PILOT ELECTRONIC NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411353343.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-04-18
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

In the prior art, silicon carbide polishing is expensive and difficult to achieve efficient polishing under weak acidic or alkaline conditions, especially when using nanoscale α-alumina abrasive suppliers are scarce and expensive, and the removal rate of traditional polishing liquids in different pH ranges is poor.

Method used

The polishing composition containing rutile titanium dioxide, calcium ions and permanganate is used to adjust the pH value between 3 and 12, and the synergistic effect of calcium ions and rutile titanium dioxide is used to improve the polishing efficiency of silicon carbide.

Benefits of technology

The cost of silicon carbide polishing is significantly reduced, and the removal rate comparable to that of strongly acidic polishing liquid is achieved in the weak acid to alkaline range, reducing the risk of surface scratches.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of silicon carbide polishing, and in particular to a silicon carbide polishing composition and a polishing method thereof. The polishing composition comprises the following components: rutile titanium dioxide; permanganate; calcium ions; water; the pH value of the polishing composition is greater than 2 and less than 13. The silicon carbide polishing method comprises: providing a silicon carbide surface to be polished, introducing the above-mentioned polishing composition between the silicon carbide surface and the polishing surface of a polishing tool, and making the silicon carbide surface contact with the polishing surface of the polishing tool and move relatively. The silicon carbide polishing composition of the present application can be used for polishing silicon carbide, and has the advantage of fast polishing rate for silicon carbide under weakly acidic or alkaline conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon carbide polishing, in particular to a silicon carbide polishing composition and a polishing method thereof. Background Art

[0002] As a third-generation semiconductor, silicon carbide is widely used in power devices and radio frequency devices. In the silicon carbide device industry chain, silicon carbide substrates account for more than half of the total cost, because silicon carbide crystal growth and cutting, grinding and polishing are very difficult, time-consuming and energy-consuming. Among them, after silicon carbide crystals are sliced, they need to be ground, rough polished, fine polished and cleaned to achieve the surface flatness and cleanliness required for devices. The goal of rough polishing is to remove the damage layer caused by grinding as quickly as possible and reduce the roughness to below Ra 0.2nm.

[0003] Since silicon carbide has a Mohs hardness greater than 9 and stable chemical properties, it is very difficult to polish. To achieve the purpose of rough polishing, the mainstream solution is to use α-alumina with a hardness equivalent to that of silicon carbide as an abrasive. However, α-alumina is prone to surface scratches. In order to control surface scratches, it is necessary to use narrowly distributed spherical nano-scale α-alumina, such as the grinding composition disclosed in patent announcement number CN111868201B, and the composition and method for material removal operation disclosed in CN114341286A. However, the preparation of spherical nano-scale α-alumina is very difficult, and there are only a handful of industrialized suppliers in the world. Basically, the cost of nano-scale α-alumina is more than 10 times that of micron-scale, and the market price is very expensive, and the cost of using it for silicon carbide polishing is very high.

[0004] On the other hand, the pH range of the polishing liquid used for silicon carbide polishing is very wide, ranging from pH 1.5 to greater than 10. Generally speaking, the removal rate of silicon carbide decreases significantly with the increase of pH. Strong acid polishing liquid usually has a higher rate than weak acid or alkaline polishing liquid, but it also has high corrosion protection requirements for the polishing machine. Many silicon carbide substrate manufacturers have a great demand for weak acid or alkaline polishing liquid. How to improve the polishing rate of weak acid or alkaline polishing liquid is a problem that urgently needs to be solved. Summary of the invention

[0005] In order to improve the polishing rate of weakly acidic or alkaline polishing liquid, the present invention provides a silicon carbide polishing composition and a polishing method thereof in view of the problems of the prior art.

[0006] In a first aspect, the present application provides a silicon carbide polishing composition, which adopts the following technical solution:

[0007] A silicon carbide polishing composition, comprising the following components:

[0008] Rutile titanium dioxide;

[0009] Permanganate;

[0010] Calcium ions;

[0011] water;

[0012] The pH value of the polishing composition is greater than 2 and less than 13.

[0013] Preferably, the polishing composition comprises the following components:

[0014] 0.1-5% by weight of rutile titanium dioxide;

[0015] 1-6% by weight of permanganate;

[0016] Calcium ions in a concentration range of 5-100 mmol / L;

[0017] The balance is water;

[0018] The pH value of the polishing composition is between 3 and 12.

[0019] Preferably, the weight percentage of the rutile titanium dioxide abrasive in the polishing composition is 0.5-5%.

[0020] The weight percentage of the permanganate is 4-6%.

[0021] The calcium ion concentration ranges from 20 to 90 mmol / L.

[0022] The calcium ions are provided by one or a mixture of several combinations of calcium chloride, calcium nitrate and calcium acetate.

[0023] The pH value of the polishing composition is in the range of 6-10.

[0024] Preferably, the pH of the polishing composition is adjusted using one of nitric acid and potassium hydroxide.

[0025] Preferably, the permanganate is potassium permanganate.

[0026] Preferably, the z-average particle size of the rutile titanium dioxide is in the range of 100-250 nanometers.

[0027] In a second aspect, the present application provides a silicon carbide polishing method, which adopts the following technical solution:

[0028] A silicon carbide polishing method comprises providing a silicon carbide surface to be polished, introducing the above-mentioned polishing composition between the silicon carbide surface and the polishing surface of a polishing tool, and making the silicon carbide surface contact with the polishing surface of the polishing tool and move relatively.

[0029] In summary, the present invention includes the following beneficial technical effects:

[0030] Nano-scale titanium dioxide can be obtained at low cost on the market, and its Mohs hardness is 5.5-7, which is significantly lower than the hardness of silicon carbide, so the probability of scratching the surface of silicon carbide is very small. In addition, the present invention finds that calcium ions and rutile titanium dioxide abrasives have a unique synergistic effect on silicon carbide polishing in a weakly acidic to alkaline environment, which can greatly reduce costs while improving polishing efficiency. DETAILED DESCRIPTION

[0031] As used herein, the terms "consisting of," "including," "comprising," "having," "having" or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a process, method, article, or apparatus that comprises a list of features is not necessarily limited to only those features but may include other features not expressly listed or inherent to such process, method, article, or apparatus.

[0032] As used herein, unless otherwise expressly stated, "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following may satisfy condition A or B: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). The application is further described in detail below.

[0033] The invention discloses a silicon carbide polishing composition and a polishing method thereof. The polishing composition comprises the following components: abrasive, calcium ions, an oxidant and water.

[0034] Abrasive: Rutile titanium dioxide is used as abrasive. The present invention has no special requirements for the particle size of rutile titanium dioxide, and ordinary technicians in this profession can select a suitable particle size range according to needs. Generally speaking, if the particle size is too large, there will be risks of polishing liquid stratification, polishing surface scratches and high roughness; if the particle size is too small, the removal rate may be insufficient. The optional average particle size of rutile titanium dioxide is less than 1 micron, more preferably less than 500 nanometers, more preferably less than 300 nanometers, and more preferably less than 250 nanometers. The optional average particle size of rutile titanium dioxide is greater than 10 nanometers, preferably greater than 50 nanometers, and more preferably greater than 100 nanometers. The abrasive can also be mixed with rutile titanium dioxide particles of different particle size distributions. The optional amount of rutile titanium dioxide added is not more than 20% by weight, and more preferably not more than 5%. Too high a rutile titanium dioxide content may reduce the dispersion stability of the polishing liquid and increase the cost. The optional amount of rutile titanium dioxide added is not less than 0.1% by weight, preferably not less than 0.5%, and more preferably not less than 1.0%. If the content of rutile titanium dioxide is too low, the polishing rate may be too low. Those skilled in the art can also mix rutile titanium dioxide with other abrasives, such as α-alumina, other phases of aluminum oxide (δ, γ, θ, η, etc.), intermediate aluminum oxide, cerium oxide, silicon dioxide, zirconium oxide, manganese oxide, silicon carbide, boron carbide, boron nitride, diamond, etc.

[0035] Calcium ions: The inventors have made unremitting efforts to find that calcium ions have an unexpected synergistic effect with and only with rutile titanium dioxide in the range of weak acidity to alkalinity on the polishing of silicon carbide, but have no synergistic effect with anatase titanium dioxide or other commonly used abrasives such as aluminum oxide, cerium oxide, etc. Therefore, the polishing composition of the present invention requires that a calcium-containing compound be used to provide calcium ions, preferably calcium salts with high solubility in water such as titanium chloride, titanium nitrate, and titanium acetate; the concentration range of calcium ions is preferably 5-200mmol / L, more preferably 10-150mmol / L, and more preferably 20-90mmol / L. If the concentration of calcium ions is too low, the synergistic effect is not obvious, and if the concentration is too high, there is a risk of reducing the colloidal stability of the polishing liquid. Those skilled in the art can also use calcium compounds with low water solubility such as calcium carbonate and calcium hydroxide to react with acids to generate calcium ions.

[0036] Oxidant: Permanganate is used as the oxidant, preferably potassium permanganate. The optional amount of the oxidant added is not more than 10% by weight, and more preferably not more than 6%. Too high an oxidant content may cause the polishing liquid to be highly corrosive and unstable. The optional amount of the oxidant added is not less than 1% by weight, preferably not less than 2%, and more preferably not less than 4%. Too low an oxidant content may result in a too low polishing rate. Those of ordinary skill in the art may also mix the permanganate oxidant with other oxidants, such as peroxides, persulfates, perhalates, hypohalites, ferrates, etc.

[0037] Water: There is no special requirement for water. Tap water, distilled water, deionized water, or water purified by other methods can be used according to the application.

[0038] pH: The inventors have found that the synergistic effect of calcium ions and rutile titanium dioxide on silicon carbide polishing is obvious in a wide pH range, but is not obvious or ineffective under strong acid or strong base conditions. Therefore, the pH is required to be greater than 2 and less than 13, preferably between 3 and 12. From the perspective of machine corrosion, it is more preferably between 6 and 10. Since the natural pH of the polishing composition is between 6 and 10, it can be used directly without adjusting the pH, or it can be adjusted with acid or alkali. There are no special requirements for the pH adjuster, as long as it can stably coexist with the oxidant, such as nitric acid, sulfuric acid, phosphoric acid, etc. for adjusting acidity, and sodium hydroxide, potassium hydroxide, quaternary ammonium hydroxide such as tetramethylammonium hydroxide, etc. for adjusting alkalinity.

[0039] Other additives: A person skilled in the art may selectively add a dispersant, a suspending agent, a metal catalyst or a surfactant. Commonly used dispersants are water-soluble compounds containing carboxyl, phosphonic acid or sulfonic acid groups, such as carboxylic acid, ethylenediaminetetraacetic acid, propylenediaminetetraacetic acid, polycarboxylic acid, copolymers of carboxylic acid and sulfonic acid, amino acids, aminomethylphosphonic acid, aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, hexamethylenediaminetetramethylenephosphonic acid, diethylenetriaminepentamethylphosphonic acid, alkylsulfonic acid, alkylsulfonic acid with substituted groups on the alkyl group, and the corresponding soluble salts thereof. Commonly used suspending agents include polyacrylic acid compounds such as polyacrylic acid, polyacrylamide, etc., modified cellulose compounds such as carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, etc., polysaccharide compounds such as guar gum, gum arabic, xanthan gum, welan gum, locust bean gum, tara gum, diutan gum, chitosan, alginic acid, etc. Commonly used metal catalysts are compounds containing high-valent metals, such as soluble salts of metals such as titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, aluminum, etc. Commonly used surfactants include anionic surfactants containing carboxyl, sulfonic acid or phosphonic acid groups, cationic surfactants containing quaternary amine groups, nonionic surfactants containing polyethers, polyethylene oxide or propylene oxide, and amphoteric surfactants of betaine type, amino acid type, imidazoline type or amine oxide type.

[0040] The present application is further described in detail below with reference to the embodiments.

[0041] Example

[0042] Example 1

[0043] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 67.8 g of potassium permanganate was added under stirring. After complete dissolution, 56.5 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 45 mmol / L (millimoles per liter), and the pH was 7.11. After the composition was mixed evenly, the polishing experiment was carried out without adjusting the pH. The polishing machine was a single-sided polishing machine with a large plate diameter of 380 mm and a non-woven polishing pad with an XY groove. Each time, a 4-inch 4H-silicon carbide substrate was polished on its silicon surface, and the pressure was 191 g / cm 2 The disk speed was 100 rpm, the polishing liquid flow rate was 60 ml / min, the polishing liquid was recycled, the polishing time was 1 hour, the removal amount was measured by an electronic balance with an accuracy of 0.1 mg, and the z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0044] Example 2

[0045] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 65.2 g of potassium permanganate was added under stirring. After complete dissolution, 16.3 g of rutile titanium dioxide with a z-average particle size of 210 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 7.77. Potassium hydroxide was added to adjust the pH of the composition to 8.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0046] Example 3

[0047] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 64.8 g of potassium permanganate was added under stirring. After complete dissolution, 10.8 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 7.95. Nitric acid was added to adjust the pH of the composition to 3.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0048] Example 4

[0049] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 67.8 g of potassium permanganate was added under stirring. After complete dissolution, 56.5 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 7.12. Potassium hydroxide was added to adjust the pH of the composition to 10.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0050] Example 5

[0051] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 67.8 g of potassium permanganate was added under stirring. After complete dissolution, 56.5 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 7.12. Potassium hydroxide was added to adjust the pH of the composition to 12.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0052] Example 6

[0053] 1.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 64.0 g of potassium permanganate was added under stirring. After complete dissolution, 1.1 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 9 mmol / L, and the pH was 8.88. Nitric acid was added to adjust the pH of the composition to 8.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0054] Example 7

[0055] 10.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 42.8 g of potassium permanganate was added under stirring. After complete dissolution, 16.0 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 90 mmol / L, and the pH was 7.28. Potassium hydroxide was added to adjust the pH of the composition to 8.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0056] Example 8

[0057] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 20.6 g of potassium permanganate was added under stirring. After complete dissolution, 5.2 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 7.32. Potassium hydroxide was added to adjust the pH of the composition to 8.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0058] Example 9

[0059] 5.0 g of anhydrous calcium nitrate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 42.5 g of potassium permanganate was added under stirring. After complete dissolution, 16.0 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 31 mmol / L, and the pH was 7.64. Potassium hydroxide was added to adjust the pH of the composition to 8.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0060] Example 10

[0061] 5.0 g of anhydrous calcium acetate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 42.5 g of potassium permanganate was added under stirring. After complete dissolution, 16.0 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 32 mmol / L, and the pH was 9.21. Nitric acid was added to adjust the pH of the composition to 8.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0062] Embodiment 11

[0063] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 65.2 g of potassium permanganate was added under stirring. After complete dissolution, 16.3 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 7.76. Nitric acid was added to adjust the pH of the composition to 6.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0064] Comparative Example

[0065] Comparative Example 1

[0066] 67.4 g of potassium permanganate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 56.2 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 0 mmol / L, the pH was 8.29, nitric acid was added to adjust the pH of the composition to 7.1, and the composition was mixed uniformly and then polished. The polishing conditions were the same as in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0067] Comparative Example 2

[0068] 64.9 g of potassium permanganate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 16.2 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 0 mmol / L, the pH was 8.67, nitric acid was added to adjust the pH of the composition to 8.0, and the composition was mixed uniformly and then polished. The polishing conditions were the same as in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0069] Comparative Example 3

[0070] 6.7 g of sodium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 65.3 g of potassium permanganate was added under stirring. After complete dissolution, 16.3 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 0 mmol / L, and the pH was 8.44. Nitric acid was added to adjust the pH of the composition to 8.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0071] Comparative Example 4

[0072] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 65.2 g of potassium permanganate was added under stirring. After complete dissolution, 16.3 g of anatase titanium dioxide with a z-average particle size of about 430 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 6.99. Potassium hydroxide was added to adjust the pH of the composition to 8.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0073] Comparative Example 5

[0074] 64.9 g of potassium permanganate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 16.2 g of anatase titanium dioxide with a z-average particle size of about 430 nm was added, at which time the calcium ion concentration was about 0 mmol / L and the pH was 6.67. Potassium hydroxide was added to adjust the pH of the composition to 8.0, and the composition was mixed evenly and then polished. The polishing conditions were the same as in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0075] Comparative Example 6

[0076] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 65.2 g of potassium permanganate was added under stirring. After complete dissolution, 16.3 g of aluminum oxide with a z-average particle size of about 230 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 5.75. Potassium hydroxide was added to adjust the pH of the composition to 8.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of aluminum oxide was measured by dynamic light scattering.

[0077] Comparative Example 7

[0078] 64.9 g of potassium permanganate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 16.2 g of aluminum oxide with a z-average particle size of about 230 nm was added, at which time the calcium ion concentration was about 0 mmol / L and the pH was 5.79. Potassium hydroxide was added to adjust the pH of the composition to 8.0, and the composition was mixed uniformly and then polished. The polishing conditions were the same as those in Example 1. The z-average particle size of aluminum oxide was measured by dynamic light scattering.

[0079] Comparative Example 8

[0080] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 65.2 g of potassium permanganate was added under stirring. After complete dissolution, 16.3 g of cerium dioxide with a z-average particle size of about 110 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 8.54. Nitric acid was added to adjust the pH of the composition to 8.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of cerium dioxide was measured by dynamic light scattering.

[0081] Comparative Example 9

[0082] 64.9 g of potassium permanganate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 16.2 g of cerium dioxide with a z-average particle size of about 110 nm was added, at which time the calcium ion concentration was about 0 mmol / L and the pH was 6.38. Potassium hydroxide was added to adjust the pH of the composition to 8.0, and the composition was mixed evenly and then polished. The polishing conditions were the same as in Example 1. The z-average particle size of cerium dioxide was measured by dynamic light scattering.

[0083] Comparative Example 10

[0084] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 65.2 g of potassium permanganate was added under stirring. After complete dissolution, 16.3 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 7.72. Nitric acid was added to adjust the pH of the composition to 2.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0085] Comparative Example 11

[0086] 64.9 g of potassium permanganate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 16.2 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added, at which time the calcium ion concentration was about 0 mmol / L and the pH was 8.68. Nitric acid was added to adjust the pH of the composition to 2.0, and the composition was mixed evenly and then polished. The polishing conditions were the same as in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0087] Comparative Example 12

[0088] 5.0 g of anhydrous calcium chloride was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 67.8 g of potassium permanganate was added under stirring. After complete dissolution, 56.5 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added. At this time, the calcium ion concentration was about 45 mmol / L, and the pH was 7.13. Potassium hydroxide was added to adjust the pH of the composition to 13.0. After the composition was mixed evenly, a polishing experiment was carried out, and the polishing conditions were the same as those in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0089] Comparative Example 13

[0090] 67.4 g of potassium permanganate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 56.2 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added, at which time the calcium ion concentration was about 0 mmol / L and the pH was 8.32. Potassium hydroxide was added to adjust the pH of the composition to 13.0, and the composition was mixed uniformly and then polished. The polishing conditions were the same as in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0091] Comparative Example 14

[0092] 64.5 g of potassium permanganate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 10.8 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added, at which time the calcium ion concentration was about 0 mmol / L and the pH was 8.77. Nitric acid was added to adjust the pH of the composition to 3.0, and the composition was mixed evenly and then polished. The polishing conditions were the same as in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0093] Comparative Example 15

[0094] 67.4 g of potassium permanganate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 56.2 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added, at which time the calcium ion concentration was about 0 mmol / L and the pH was 8.28. Potassium hydroxide was added to adjust the pH of the composition to 10.0, and the composition was mixed uniformly and then polished. The polishing conditions were the same as in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0095] Comparative Example 16

[0096] 67.4 g of potassium permanganate was added to 1000.0 g of deionized water, stirred to completely dissolve, and then 56.2 g of rutile titanium dioxide with a z-average particle size of about 210 nm was added, at which time the calcium ion concentration was about 0 mmol / L and the pH was 8.29. Potassium hydroxide was added to adjust the pH of the composition to 12.0. After the composition was mixed evenly, a polishing experiment was performed, and the polishing conditions were the same as in Example 1. The z-average particle size of titanium dioxide was measured by dynamic light scattering.

[0097] Performance testing

[0098] Table 1: Ingredient content and test data of Examples 1-11 and Comparative Examples 1-16

[0099]

[0100]

[0101]

[0102] From Example 1 and Comparative Example 1, Example 2 and Comparative Examples 2-3 and Table 1, it can be seen that when calcium chloride is added to the polishing composition containing rutile titanium dioxide abrasive, the polishing removal rate of silicon carbide by the polishing composition is greatly increased, while adding sodium chloride with the same chloride ion equivalent cannot increase the removal rate, indicating that the component that increases the polishing rate of silicon carbide is calcium ions.

[0103] From Examples 1-11, Comparative Examples 4 and 5, Comparative Examples 6 and 7, Comparative Examples 8 and 9 and Table 1, it can be seen that the accelerating effect of calcium ions on the polishing of silicon carbide is only apparent when the abrasive of the polishing composition uses rutile titanium dioxide, while it is not apparent when other abrasives such as anatase titanium dioxide, aluminum oxide, cerium dioxide, etc. are used. This indicates that the polishing composition using rutile titanium dioxide and calcium ions can have an unexpected synergistic effect on the polishing rate of silicon carbide, and can significantly improve the polishing rate of silicon carbide.

[0104] Combining Comparative Examples 10 and 11, Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, Example 3 and Comparative Example 14, Example 4 and Comparative Example 15, Example 5 and Comparative Example 16, Comparative Example 12 and Comparative Example 13 and Table 1, it can be seen that the synergistic effect of calcium ions and rutile titanium dioxide abrasive on silicon carbide polishing is obvious between pH 3 and pH 12, but not obvious or no synergistic effect at pH 2 or 13.

[0105] Combining Examples 1-11 and Comparative Examples 10-11 with Table 1, it can be seen that the polishing composition containing rutile titanium dioxide abrasive and calcium ions can achieve the effect of a strong acid polishing liquid in the polishing of silicon carbide in the range of weak acidity to alkalinity.

[0106] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention is disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments according to the technology of the present invention are within the scope of the technical solution of the present invention without departing from the content of the technical solution of the present invention.

Claims

1. A silicon carbide polishing composition, characterized in that: The polishing composition comprises the following components: 0.5-5% by weight of rutile titanium dioxide; 4-6% by weight of permanganate; Calcium concentration ranges from 20-90 mmol / L; The balance is water; The pH value of the polishing composition is between 3 and 12.

2. A silicon carbide polishing composition according to claim 1, characterized in that: The pH value of the polishing composition is in the range of 6-10.

3. A silicon carbide polishing composition according to claim 1, characterized in that: The pH of the polishing composition is adjusted using one of nitric acid and potassium hydroxide.

4. A silicon carbide polishing composition according to claim 1, characterized in that: The permanganate is potassium permanganate.

5. A silicon carbide polishing composition according to claim 1, characterized in that: The calcium ions are obtained by dissolving one or a mixture of several of calcium chloride, calcium nitrate and calcium acetate in water.

6. A silicon carbide polishing composition according to claim 1, characterized in that: The z-average particle size of the rutile titanium dioxide is in the range of 100-250 nanometers.

7. A silicon carbide polishing method, characterized in that: A silicon carbide surface to be polished is provided, the polishing composition according to any one of claims 1 to 6 is introduced between the silicon carbide surface and the polishing surface of a polishing tool, and the silicon carbide surface and the polishing surface of the polishing tool are brought into contact and relatively moved.

Citation Information

Patent Citations

  • Grinding composition

    CN111868201B

  • Compositions and methods for performing material removal operations

    CN114341286A

  • Polishing solution as well as preparation method and application thereof

    CN114410226A

  • Chemical mechanical polishing solution and use method thereof

    CN114686113A

  • Polishing solution for grinding silicon carbide substrate, polishing solution set and grinding method

    CN115975511A